Growth and Yield of Arrowroot Intercropped in Coconut Garden as Influenced by Organic Management - Swadija, O. K; Padmanabhan, V. B; kumar, Vijayaraghava (JOURNAL OF ROOT CROPS, 2014)
Field experiments were conducted during 2007-2008 and 2008-2009 in the identified five panchayats, viz., Parassala, Pallichal, Kattakkada, Poovachal and Pullempara in the Western Ghat region of Thiruvananthapuram district for deriving an organic nutrient schedule for sustained yield of arrowroot (Maranta arundinacea L.) intercropped in coconut garden. Seven treatments were laid out in randomized block design with three replications. The treatments consisted of FYM @ 10 t ha-1, 15 t ha-1 and 10 t ha-1 + organic sources to substitute NPK @ 50: 25:75 kg ha-1 each with and without biofertilizers (Azospirillum and phosphobacteria) along with absolute control. The results indicated that arrowroot can be profitably intercropped in coconut gardens. Higher rhizome yield (18.62 t ha-1), net income (` 74,450 ha-1) and benefit:cost ratio (1.99) could be obtained by the application of FYM @ 15 t ha-1 + biofertilizers.